Hyponatremia, falls and bone fractures: A systematic review and meta‐analysis. (12th July 2018) - Corona, Giovanni; Norello, Dario; Parenti, Gabriele; Sforza, Alessandra; Maggi, Mario; Peri, Alessandro
Summary: Objective: To perform a meta‐analysis based on published studies that compared falls and bone fractures between patients with and without hyponatremia. Context: There is evidence suggesting that hyponatremia is associated with an increased risk of falls and bone fractures. Design: An extensive Medline, Embase and Cochrane search was performed to retrieve all studies published up to, 30 April 2017, using the following words: "hyponatremia" or "hyponatraemia" AND "falls" and "bone fractures." A meta‐analysis was performed including all studies comparing falls and bone fractures in subjects with or without hyponatremia. Patients and Results: Of 216 retrieved articles, 15 studies satisfied inclusion criteria encompassing a total of 51 879 patients, of whom 2329 were hyponatremic. Across all studies, hyponatremia was associated with a significantly increased risk of falls (MH‐OR = 2.14[1.71; 2.67]. This result was confirmed when only hospitalized patients were considered (MH‐OR = 2.44 [1.97; 3.02]). A meta‐regression analysis showed that the hyponatremia‐related risk of falls was higher in those studies considering a lower serum [Na + ] cut‐off to define hyponatremia. Interestingly, the estimated risk of falls related to hyponatremia was already significantly higher when a serum [Na + ] cut‐off of 135 mmol/L was considered (MH‐OR = 1.26[1.23;1.29]). The presence of hyponatremia was also associated with a higher risk of fractures, particularly hip fractures (MH‐OR = 2.00[1.43;2.81]). Conclusions: This study confirms that hyponatremia is associated with an increased risk of falls and bone fractures. The clinical, social and economic relevance of such association is strengthened by the increased incidence of hyponatremia in older people.